Postmortem acinar autolysis in rat sublingual gland: a morphometric study - Leticia Rodrigues Nery; Carla Ruffeil Moreira; Tania Mary Cestari; Rumio Taga; José Humberto Damante (University of São Paulo, 2010)
ABSTRACT OBJECTIVE: To analyze and to quantify morphological acinar postmortem changes in rat sublingual glands (SLG). MATERIAL AND METHODSs: Fifty rats were divided into two groups of 25 animals each. Group I was used for morphological and morphometric evaluations and group II for the determination of gland density and processed gland volume. Acinar autolytic changes were studied at 0 (control group), 3, 6, 12 and 24 h postmortem periods. The morphometric analysis of the volume density (Vv) and total volume (Vt) of intact (ia) and autolyzed (aa) acini was performed under light microscopy using a Zeiss II integration grid with 100 symmetrically distributed points. RESULTS: Morphologically, temporal progressive nuclear alterations and gradual loss of the structural architecture of acinar cells were found. Regarding quantitative results, both the Vvaa and the Vvia showed statistically significant differences among all postmortem periods (p<0.05). Vvaa increased from 0.42% at 0 h to 75.84% at 24 h postmortem and Vvia decreased from 71.16% to 0% over the same period. For Vtaa and Vtia, no statistically significant differences occurred between 12-24 h and 0-3 h (p>0.05), respectively. Vtaa increased from 0.18 mm³ at 0 h to 38.17 mm³ at 12 h, while Vtia showed a decrease from 33.47 mm³ to 0 mm³ between 3-24 h postmortem. Data concerning Vtaa were adjusted by two-variable linear regression, obtaining the equation: y=-3.54 + 3.38x (r²=0.90). The Vtaa growth rate calculated by this equation was 3.38 mm³/h between 0-12 h. CONCLUSION: Acinar autolysis on rat SLG demonstrated the most significant signs during the first 6 h postmortem and was widely spread through the gland at 12 h.